TheImpact of Personal and Family Allowances on Income Tax Performance in Iraq (Kurdistan Region - Iraq as an Example) - Yaba, Dr. Kamal Anwar; Amin, Dr. Salah El-Din Ahmed Mohamed (Journal of Legal and Political Studies, 2018)
The contemporary financial thought has come down to address tax exemption within the framework of the fair taxation system and the extent that this system takes into account that taxation should be based on the personality of taxpayer, meaning the standing of the taxpayer and the financial, social and familial considerations related to him or her. and this system occupies significant status within the basic rules of taxation, due to its role in determining the taxpayer’s ability and ascertaining taxation pressure that both are affected by tax rate, tax exemption personal and family and other various exemptions, which are related to the way of dealing with sources of income in a fashion that will impact the tax performance. The significance of tax exemptions appears through the definition and explanation of its types during the application of the amended Iraqi Taxation law (N. 113 in 1982) and its impact on the tax performance in Kurdistan region. Therefore, this study has been divided into three sections, in section one the definition of personal and family tax exemptions has been provided. In section two, types of tax exemptions and their beneficiaries has been addressed, section three has been dedicated to analysis of tax legislation in Kurdistan region through examination of the implications of its implementations and its impact on the tax system, taxpayers and the financial authority. At the end, a bunch of conclusions and recommendations have been presented regarding this subject.
Keywords: tax exemption; taxation; sources of income; tax performance